Molecular genetics in autism spectrum disorder: a case series - Placid, Chris; P. V., Rinsy; George, Manju (International Journal of Contemporary Pediatrics, 2022)
Autism spectrum disorder (ASD) has emerged as a fairly common yet heterogeneous condition. More evidence towards a large number of specific genetic variations in ASD are now identified. Often we encounter difficulties in counselling the parents on the disease origin. We present a case series of 6 children including a pair of twin sibling who were diagnosed as ASD with a definite genetic aetiology. These children belonged to the age group of 3 to 15 years and were diagnosed as ASD as per DSM V criteria. Of the 6 children, two were otherwise clinically normal and remaining four children had associated medical conditions including hypocalcemia, severe hypotonia, seizures, cardiomyopathy, intellectual disability and neuroregression. In view of an unrecognised aetiology and children being first born in the family, parents were counselled for a genetic evaluation. Genetic test reports revealed gene variation pathogenic for ASD, of which 4 of them had known syndromic association. Though intervention would mostly remain the same, genetic aetiology helped us in prognosticating and improved the family’s outlook towards the disease. Hence it is desirable to identify genetic variations in all possible ASD cases as it has the potential to improve family planning, trigger screening for co-occurring medical problems, aid the prognosis, and start specific interventions.